1967
DOI: 10.1152/ajplegacy.1967.212.6.1461
|View full text |Cite
|
Sign up to set email alerts
|

Systemic arterial blood pressure and pulse rate in chronically restrained rhesus monkeys

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…Mean control values ±SD for a number of variables are included in Tables 2 and 3. These data agree with normal values found by others (10,11), except that our monkeys had a higher heart rate and lower hematocrit.…”
Section: Cardiovascular Alterations--the Monkeyssupporting
confidence: 93%
“…Mean control values ±SD for a number of variables are included in Tables 2 and 3. These data agree with normal values found by others (10,11), except that our monkeys had a higher heart rate and lower hematocrit.…”
Section: Cardiovascular Alterations--the Monkeyssupporting
confidence: 93%
“…All experiments were performed a minimum of 7-10 days postoperatively to avoid the cardiovascular effects of recent surgical procedures and anesthesia. Monkeys have been shown to remain stable for several months under these conditions (14). Details of this preparation have been reported previously (15).…”
Section: Methodsmentioning
confidence: 90%
“…Baseline heart rate and blood pressure recorded for the remainder of the study (after the transiently observed decreases) were similar to those reported during controlled ventilation at 1 minimum alveolar concentration in halothane-and isoflurane-anesthetized monkeys 1,2 and lower than those reported for awake chronically instrumented monkeys. 13,14 Although significant changes were recorded, clinically relevant changes in ventilator-controlled breaths were minimal during the study. However, a progressive increase in spontaneous breathing was detected approximately 2 hours after FEN administration.…”
Section: Discussionmentioning
confidence: 99%